Near-infrared bandpass filters with improved transparency for 1000nm spectral region using sputtered silicon compound films - Orr, H; Wallace, M; Dalton, G (2008)
Near-infrared bandpass filters are commonly designed and manufactured using vacuum-evaporated films of Silicon and Silicon Monoxide. However the transparency of these filters is limited by optical absorption in the films when producing filters for wavelengths below 1200nm approximately. This work reports improvements in NIR filter transparency achieved by exploiting recent advances in magnetron sputtering technology. Sputtered silicon compound films have been used to demonstrate efficient bandpass filters for astronomy applications at wavelengths below 1000nm. This process technology allows a new selection of film materials to be used in design of NIR bandpass filters, with transmission and thermal drift characteristics which differ from conventional evaporated coatings. The spectral location of the bandpass is controlled by a non-optical method, which avoids the complex optical monitoring configurations normally required. The speed and flexibility of this process also offers a potential solution for projects which require small batches of custom NIR optical filters. Highly durable filters are obtained without elevated process temperature, which would otherwise be required in conventional evaporation processes. This avoids heating filter substrates which may be sensitive to thermal cycling effects. Attenuation of sidebands to T<0.0001 is reported across the spectral range of common sensor devices. The thermal sensitivity for cryostat applications is characterised and compared to conventional evaporated optical coatings. This method has been applied to 975nm and 985nm bandpass filters for use on VISTA project instrumentation. It also offers improvements for filters at longer wavelengths in the range 1000nm-5000nm. Some examples are reported in this region.